The Correlation between Vocabulary Mastery and Self-Confidence in Speaking English - Safitri, Merry Dian; Trisno, Edi (Journal of English Language Teaching, 2024)
This research aims to determine the correlation between vocabulary mastery and self-confidence in speaking English. This research was a correlational design. The population of this research was ten classes of second-year students enrolled in the Public Speaking course in the English Language Education Study Program at Universitas Negeri Padang from K1 2022-K10 2022. By using cluster random sampling, two classes were chosen; K6 2022 and K7 2022 as the sample of this study. The instruments of this research were a speaking test, vocabulary test, and self-confidence questionnaire. This research used quantitative research methods and the data was analyzed using SPSS 26 for Windows. The data were analyzed using the Pearson Product Moment and Multiple Linear Regression analysis techniques. It was found that the Sig. 0.212 which is more than 0.05 (> 0.05). Therefore, based on the result above, the null hypothesis was accepted and the alternative hypothesis was rejected. Thus, it can be concluded that there is no simultaneous correlation between vocabulary mastery and self-confidence in speaking English in the Public Speaking class.